2008
DOI: 10.1177/0047287508321195
|View full text |Cite
|
Sign up to set email alerts
|

Standard Hospitality Elements at Resorts

Abstract: Prior research investigating the factors important to resort visitors has generally focused on a specific resort setting or market segment, which has resulted in a tendency to emphasize activity-related elements. While useful, this tendency to emphasize activity-related elements has limited our understanding of the role of the nonactivity, hospitality-based elements common to all resort types. Given this gap in the research literature, the purpose of this study is to develop a better understanding of the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
9
0
5
Order By: Relevance
“…Given the claims made that there is significant growth in demand for wellness tourism (Smith and Puczko 2009), we might expect to see a range of features of wellness tourism provision added to tourism more generally and this does seem to be the case (Brey et al 2008). This might make it difficult to identify wellness tourism from a solely supplyside perspective.…”
Section: Wellness Tourismmentioning
confidence: 99%
“…Given the claims made that there is significant growth in demand for wellness tourism (Smith and Puczko 2009), we might expect to see a range of features of wellness tourism provision added to tourism more generally and this does seem to be the case (Brey et al 2008). This might make it difficult to identify wellness tourism from a solely supplyside perspective.…”
Section: Wellness Tourismmentioning
confidence: 99%
“…Research also reveals all manner of travel determinants based on the decision context, such as resorts (Brey et al 2008) or ski destinations (Konu, Laukkanen, and Komppula 2011).…”
Section: Cruise Determinantsmentioning
confidence: 99%
“…For instance, when consumers seek to enjoy sun, sea, and sand they ultimately choose properties that provide these amenities. However, recent research has identified that while the activity driven concept plays an important role in resort selection, tertiary features or standard resort hospitality elements (SRHE) also represent important property factors (Brey et al, 2008). In their initial study of these secondary elements, three factors emerged from the 18 universal hospitality elements at resorts.…”
Section: Standard Resort Hospitality Elementsmentioning
confidence: 99%
“…Performance satisfaction, values representing the more traditional IPA methodology, identified approximately 8 elements performing below expected levels. The majority of these elements are feature-based, identified as the most important tertiary resort elements (Brey et al, 2008). Finally, relative performance provided an alternative attribute evaluation as performance was compared against a competitive resort.…”
Section: Journal Of Tourism Insight Smentioning
confidence: 99%
See 1 more Smart Citation